Respuesta :

Answer:  see proof below

Step-by-step explanation:

Given: A + B + C = π                →      A + B = π - C

                                                         A + C = π - B

                                                         B + C = π - A

Cofunction Identities:       sin [(π/2) - A] = cos A

                                          cos [(π/2) - A] = sin A

Sum to Product Identity:   sin A - sin B = 2 cos [(A + B)/2] · sin [(A - B)/2]

Pythagorean Identity:       cos²A + sin²A = 1    →   cos²A = 1 - sin²A

Even/Odd Identity:           cos (-A) = -cos(A)

Double Angle Identity:     cos (2A) = 2 cos²A - 1

Proof LHS → RHS:

LHS:                      cos [(B + C) - A] - cos [(A + C) - B] + cos [(A + B) + C]

Given:                   cos [(π - A) - A] - cos [(π - B) - B]  + cos [(π - C) - C]

                         =  cos (π -2A) - cos (π -2B) + cos (π -2C)

Cofunction:          cos (-2A)  - cos (-2B) + cos (-2C)

Even/Odd:            -cos (2A) + cos (2B) - cos (2C)

Double Angle:     -(2cos²A - 1) + cos (2B) - cos (2C)

                           = 1 - 2cos²A + cos (2B) - cos (2C)

Sum to Product:    1 - 2cos²A - 2sin(B+C) · sin (B-C)

Given:                     1 - 2cos²A - 2sin (π - A) · sin (B - C)

Cofunction:             1 - 2cos²A - 2sin A · sin (B - C)

Pythagorean:         1 - 2(1 - sin²A) - 2sin A · sin (B - C)

                            = 1 - 2 + 2sin²A - 2sin A · sin (B - C)

                            =     -1 + 2sin²A - 2sin A · sin (B - C)

Factor:                        -1 + 2sin A (sin A - sin (B - C))

Given:                     -1 + 2sin A [sin (π - (B + C)) - sin (B - C)]    

Cofunction:             -1 + 2sin A [sin (B + C) - sin (B - C)]  

Sum to Product:      -1 + 2sin A [2 cos B · sin C]  

                               = -1 + 4sin A · cos B · sin C

LHS = RHS  [tex]\checkmark[/tex]

                                                       

Ver imagen tramserran
Ver imagen tramserran